2018
DOI: 10.1136/ejhpharm-2017-001412
|View full text |Cite
|
Sign up to set email alerts
|

Stability of mixtures of ondansetron and haloperidol stored in infusors at different temperatures

Abstract: Background and objectiveMixing different drugs for use in continuous infusion systems is a common practice in palliative care, but analytical study of compatibility and stability is not always available. The objective of this work is to study the stability of solutions of ondansetron and haloperidol at different concentrations and temperatures all prepared in 0.9% NaCl and stored in infusors, with all cases protected from light.Materials and methodsThe high performance liquid chromatography-Ultraviolet (HPLC-U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…The stress sensitivity of both pure drug and drug in PN admixture is confirmed by other studies. OND is susceptible to oxidation and acid/basic hydrolysis, while it remains insensitive to decomposition under the influence of temperature at the boiling point [23,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stress sensitivity of both pure drug and drug in PN admixture is confirmed by other studies. OND is susceptible to oxidation and acid/basic hydrolysis, while it remains insensitive to decomposition under the influence of temperature at the boiling point [23,31].…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [24] developed and validated the HPLC-DAD (diode array detector) method for the simultaneous quantification of dexamethasone sodium phosphate, OND, granisetron, tropisetron, and azasetron hydrochlorides in infusion samples. Espinosa-Bosch et al [31] evaluated the stability and the compatibility of haloperidol and OND when stored in elastomeric infusors at two temperatures (25 and 37 • C). In 1995, Kirkham et al [32] described determination of OND in PN admixtures, but in their paper, no details are stated about sample isolation and method validation.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that levomepromazine decomposed fastest in a 0.9% NaCl solution, and the storage of morphine at 4 • C led to its precipitation [42]. Espinosa-Boch et al evaluated the stability of mixtures of haloperidol and ondansetron stored at various temperatures, confirming their stability up to 48 h after preparation [43].…”
Section: Introductionmentioning
confidence: 99%
“…The antiemetic activity of the drug is brought about through the inhibition of 5-HT3 receptors present both centrally (medullary chemoreceptor zone) and peripherally (GI tract). This inhibition of 5-HT3 receptors in turn inhibits the visceral afferent stimulation of the vomiting center, likely indirectly at the level of the area postrema, as well as through direct inhibition of serotonin activity within the area postrema and the chemoreceptor trigger zone [14][15][16].…”
Section: Introductionmentioning
confidence: 99%